The contradiction in disability law : selective abortions and rights - Nizar, Smitha (New Delhi : Oxford University Press, 2016)
This title explicates the unproblematic perception towards disability selective abortions. It demonstrates the wrongness of selective abortions, but without entering the realm of a womens right to take decisions about her body and analyses the legitimacy of automatic decision taken to abort the fetus, once diagnosed with disability.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 19, 2016).
Keywords: People with disabilities -- Legal status, laws, etc; People with disabilities -- Civil rights; Abortion -- Law and legislation; Abortion -- Moral and ethical aspects; Law; Laws of specific jurisdictions & specific areas of law